Utilization of Bioslurry on Maize Hydroponic Fodder as a Corn Silage Supplement on Nutrient Digestibility and Milk Production of Dairy Cows - Heru Dwi Nugroho; Idat Galih Permana; . Despal (Faculty of Animal Science, Bogor Agricultural University, 2015)
The research was conducted to study the effect of addition of 7% DM maize hydroponic fodder (MHF) in corn silage on digestibility and milk production of dairy cows. The experiment used a completely randomized block design with two treatments, and four replications. The treatments were dairy cows fed with grass (Pennisetum purpureum), corn silage, and concentrate (R0), and dairy cows fed with grass (P. purpureum), corn silage, concentrate, and MHF (R1). This research used eight dairy cows with initial average milk production of 13.01±2.96 L/d. MHF was produced in a hydroponic system using bioslurry as a fertilizer enriched with mineral fertilizer. Variables observed were chemical composition of bioslurry, nutrient content of ration, daily dry matter intake, nutrient digestibility, Total Digestible Nutrient (TDN), and Digestible Energy (DE). Data were analyzed with ANOVA, except for milk production using ANCOVA. Supplementation of MHF resulted a higher total dry matter intake on R1 than R0 (P<0.05), 12.99±0.063 kg/head/d, and 11.98±0.295 kg/head/d, respectively. The digestibility of nutrients were not affected by the addition of MHF. Energy consumption in R1 was also higher than R0 (P<0.05), 49.95±0.36 Mkal/kg, and 46.11±0.54 Mkal/kg, respectively. Supplementation of MHF also increased nitrogen consumption, R1 was higher than R0 (P<0.05), 318.3±2.3 g/head/d, and 295.9±3.5 g/head/d, respectively, and could maintain the persistency of milk production at the end of lactation. It can be concluded that supplementation of MHF in corn silage can increase dry matter intake, energy consumption, and nitrogen consumption, also can maintain nutrient digestibility and maintain persistency of milk production during late lactation of dairy cows.Key words: bioslurry, dairy cow, greenhouse fodder, nutrient digestibility